How life events may confer vulnerability to addiction: the role of epigenetics - Liu, Shirelle X.; Harris, Andrew C.; Gewirtz, Jonathan C. (Frontiers in Molecular Neuroscience, 2024)
Substance use disorder (SUD) represents a large and growing global health problem. Despite the strong addictive potency of drugs of abuse, only a minority of those exposed develop SUDs. While certain life experiences (e.g., childhood trauma) may increase subsequent vulnerability to SUDs, mechanisms underlying these effects are not yet well understood. Given the chronic and relapsing nature of SUDs, and the length of time that can elapse between prior life events and subsequent drug exposure, changes in SUD vulnerability almost certainly involve long-term epigenetic dysregulation. To validate this idea, functional effects of specific epigenetic modifications in brain regions mediating reinforcement learning (e.g., nucleus accumbens, prefrontal cortex) have been investigated in a variety of animal models of SUDs. In addition, the effects of epigenetic modifications produced by prior life experiences on subsequent SUD vulnerability have been studied, but mostly in a correlational manner. Here, we review how epigenetic mechanisms impact SUD-related behavior in animal models and summarize our understanding of the relationships among life experiences, epigenetic regulation, and future vulnerability to SUDs. Despite variations in study design, epigenetic modifications that most consistently affect SUD-related behavior are those that produce predominantly unidirectional effects on gene regulation, such as DNA methylation and histone phosphorylation. Evidence explicitly linking environmentally induced epigenetic modifications to subsequent SUD-related behavior is surprisingly sparse. We conclude by offering several directions for future research to begin to address this critical research gap.